Implementasi Media Puzzle Kata Pada Kurikulum Merdeka untuk Mengatasi Kesulitan Membaca Siswa Kelas I di Sekolah Dasar - Listryanto, Danang Pratama; Widiyono, Aan (BASICA Journal of Arts and Science in Primary Education, 2023)
Reading is a fundamental skill, reading does not just interpret words but involves all aspects of understanding, analyzing and all the information presented in the text. This study aims to investigate the application of word puzzle media in the independent curriculum as a solution to overcome the problem of reading difficulties. The Independent Curriculum is an innovative approach that integrates media and technology into learning, while Word Puzzle Media is a learning method that combines aspects of play with learning to read. This research uses a qualitative approach with a case study method. Data was collected through the process of observation, interviews and documentation. The sample of this research consists of first year students of SDN 5 Sekuro. The results showed that reading skills improved significantly, besides the fact that the use of this word puzzle media could increase students' interest and motivation for learning, as this media combined elements of games with reading activities, making the learning process more fun and challenging.